IMPLICATIONS OF ISLAMIC GOVERNANCE ON ISLAMIC BANK FRAUD - Ngumar, Sutjipto; Fidiana, Fidiana; Retnani, Endang Dwi (Universitas Muhammadiyah Malang)
This study was conducted to test fraud at Islamic banks in terms of Islamic Good Corporate Governance. The research data uses Islamic banks registered at Bank Indonesia from 2017 to 2018. Data of the board of directors, board of commissioners, implementation of internal controls, and the sharia supervisory board were obtained from the composite index of self assessment in GCG report. This study did not succeed in accepting that the board of directors and board of commissioners have a negative effect on fraud and proved of the negative influence of internal controls and the sharia supervisory board on fraud. The sharia supervisory board is indeed a decisive element for fraud control from the conformity aspects of implementing Islamic bank operations. The board of directors is an external party of the company that is not directly involved in the company's operations